Antibiofilm Activity of Intracellular Extracts of Westiellopsis prolifica Isolated From Local Environment in Baghdad - Shurooq Latif Al-Tmimi (Journal of Global Pharma Technology, 2018)
Acetone and hexane extracts of cyanobacteria Westiellopsis  prolifica was tested In vitro. Antibiofilm  activity was evaluated by biofilm production assay against six  pathogenic bacteria in which three are Gram- positive bacteria  "Staphylococcus aureus , B.subtilis, and Streptococcus sp. "  and three  are Gram- negative bacteria" Shigella sp., Proteus sp. and Pseudomonas aeruginosa " in additions two isolates of fungi "Aspergills niger  and Candida albicans".The results showed that crude acetone extract for W .prolifica better than hexane extract ,and  more efficient on negative gram bacteria than positive gram bacteria. The highest biofilm inhibition of acetone extract against Shigella sp. reached to (10 ) %, while lower biofilm inhibition ( 68)% against A. niger compared to hexane, with the highest biofilm inhibitory rate in C.albicans  (42 )% and lower biofilm inhibition against Proteus sp. reached to ( 98 )%.at concentration 100 µl. As well as  Congo red agar  method showed that acetone extract for W .prolifica better than hexane extract in the anti-biofilm formation at 50 µl, The best anti-biofilm activity of   acetone extract  against  B. subtilis , Shigella sp., Proteus sp. and C. albicans  (++ )While A. niger (+) showed slight  effectiveness .On the other hand the hexane extract showed little efficacy against biofilm for all studied isolates .Key words: Westiellopsis prolifica, Active compounds, Antibiofilm, Partial purification, GC/MS Analysis.